Optimising and adapting perfusion feeds in serum-free medium to intensify CAR-T cell expansion in stirred-tank bioreactors - Springuel, Pierre; Hood, Tiffany; Slingsby, Fern; Schmidberger, Timo; Bevan, Nicola; Dianat, Noushin; Hengst, Julia; Rafiq, Qasim A. (Frontiers in Bioengineering and Biotechnology, 2025)
The ex vivo expansion of autologous chimeric antigen receptor (CAR) T cells to reach a therapeutic dose significantly prolongs manufacturing time and increases overall costs. The common use of animal- or human-derived serum in T cell expansion culture media further contributes to process variability, costs and introduces additional safety concerns. To address these challenges, this study focused on intensifying CAR-T cell expansion using perfusion processes in xeno-free (XF) and serum-free (SF) culture medium. The impacts of alternative tangential flow (ATF) perfusion rates, perfusion start times and donor variability were evaluated using a Design of Experiments (DOE) approach in the Ambr® 250 High-Throughput Perfusion stirred-tank bioreactor. This allowed the identification of optimal combinations of perfusion parameters on a per-donor basis, enabling 4.5-fold improvements in final cell yields and over 50% reductions in the expansion time required to reach a representative CAR-T dose compared to a fed-batch process. Subsequent process development then established an adaptive perfusion strategy enabling 130 ± 9.7-fold expansions to achieve final cell densities of 33.5 ± 3 × 106 cells/mL while reducing medium requirements by 11% without compromising CAR-T cell quality attributes compared to static well-plate cultures. Harvested cells predominantly expressed naïve and central memory markers, low levels of exhaustion markers, and maintained cytotoxicity and cytokine release in vitro. This study demonstrates the potential of optimising and adapting perfusion strategies in XF/SF-culture medium to enhance CAR-T cell yields, shorten expansion times and reduce medium consumption while addressing patient variability in clinical manufacturing. Key considerations for future implementation and improvement of adaptive perfusion feeds for clinical CAR-T manufacturing are also discussed.